New Hampshire - Mills, Jordan (North Mankato, Minnesota Capstone Press, a capstone imprint, 2017)
"This book uses maps, full color photographs, and easy-to-read text to introduce the state of New Hampshire"--
Different countries
Includes bibliographical references and index
Grades 4-6
Ages 8-10
1 2 13
Keywords: New Hampshire -- Juvenile literature